Educação do corpo e linguagem: relações e contradições no contexto da Educação Física escolar no ensino médio - Machado, Aline Gomes (2019)
With the insertion of Physical Education in the Language area in the documents of national extent, like the National Curriculum Parameters for the Secondary Education (PCNEM), the Common National Curriculum Base (BNCC) and the National Examination of the Secondary Education (ENEM), it turns out the need to identify in which way Physical Education and language are related to the school context, specifically, in High School. So, it finds the investigation as an inquiry problem: which are the relations and existing contradictions between curriculum and pedagogical praxis in the teaching of the Physical Education as a subject of Language area in High School? The symbolic representation of physical language, when intentionally developed, in other words, from the reflected physical movement, benefits the education field, the social interaction and students knowledge construction, stimulating affection, cognition and physical expression. In these terms, the general objective of this inquiry consists in checking the relations and contradictions between curriculum and pedagogical praxis in the teaching of the Physical Education while a subject of the Language area in High School. As specific objectives, it seeks to discuss about the epistemological transformations that led to the insertion of Physical Education while subject of the Language area and its Technologies; to analyse the conception of language by the teachers of Physical Education of the State Education System in Goiás; to identify through the report of the teachers the limits and means of teaching of the school Physical Education while language; to carry out the analysis of the official documents quoted by the teachers as guiding ofthe pedagogic practice. It is shaped in a quanti-qualitative character study based on the materialistic dialectic method. The used inquiry instruments were semistructured interview, setting itself up as subjects teachers of the State Education System in Goiás who work in High School, besides the analysis of the documents quoted by the interviewed teachers. The analysis of the interviews was made through the technique of analysis of content indicating, as a synthesis, four categories that are connected to the objectives of this study: conception of language and physical language; the concept of Physical Education and the approximations with the language; the contents of the Physical Education; curriculum and pedagogical praxis: relations and contradictions. Through the analysis of the interviews and of the main guiding documents listed by the teachers, it is concluded that the discussion on Physical Education and language, in the direction of proposing pedagogical actions that justify this relation, remains like a not much explored subject, be in the academic-scientific field, be in the school context itself, when there is suggesting the insertion of this subject in the initial and continuing training of the teachers. Besides, it checks as essential that the guiding documents seek to enhance the debate on Physical Education and language, offering more concise elements for the pedagogical practice.